2013
DOI: 10.1105/tpc.112.103184
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+-Dependent Protein Kinase11 and 24 Modulate the Activity of the Inward Rectifying K+ Channels inArabidopsisPollen Tubes

Abstract: Potassium (K+) influx into pollen tubes via K+ transporters is essential for pollen tube growth; however, the mechanism by which K+ transporters are regulated in pollen tubes remains unknown. Here, we report that Arabidopsis thaliana Ca2+-dependent protein kinase11 (CPK11) and CPK24 are involved in Ca2+-dependent regulation of the inward K+ (K+  in) channels in pollen tubes. Using patch-clamp analysis, we demonstrated that K+  in currents of pollen tube protoplasts were inhibited by elevated [Ca2+]cyt. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
108
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(111 citation statements)
references
References 81 publications
(114 reference statements)
2
108
0
1
Order By: Relevance
“…A number of CDPKs have been reported to regulate ion channel activities in stomatal movement (Pei et al, 1996;Li et al, 1998;Mori et al, 2006;Geiger et al, 2010Geiger et al, , 2011Zou et al, 2010;Brandt et al, 2012;Scherzer et al, 2012), plant responses to salt stress (Latz et al, 2013), and pollen tube growth (Gutermuth et al, 2013;Zhao et al, 2013;Zhou et al, 2014). In this report, the plasma membrane localized-CPK8 showed abundant expression in stomatal guard cells ( Figure 1D; Supplemental Figure 2), indicating its potential role in regulation of stomatal movement and ion channel activity.…”
Section: Ca 2+ -Mediated Protein Phosphorylation: a Universal Regulatmentioning
confidence: 68%
See 1 more Smart Citation
“…A number of CDPKs have been reported to regulate ion channel activities in stomatal movement (Pei et al, 1996;Li et al, 1998;Mori et al, 2006;Geiger et al, 2010Geiger et al, , 2011Zou et al, 2010;Brandt et al, 2012;Scherzer et al, 2012), plant responses to salt stress (Latz et al, 2013), and pollen tube growth (Gutermuth et al, 2013;Zhao et al, 2013;Zhou et al, 2014). In this report, the plasma membrane localized-CPK8 showed abundant expression in stomatal guard cells ( Figure 1D; Supplemental Figure 2), indicating its potential role in regulation of stomatal movement and ion channel activity.…”
Section: Ca 2+ -Mediated Protein Phosphorylation: a Universal Regulatmentioning
confidence: 68%
“…As shown in Figure 7, ABA and Ca 2+ inhibition of inward K + currents were impaired in guard cells of cpk8 mutant plants. So far, at least 11 Arabidopsis CDPKs have been reported to function in regulation of ion channel activity in plant cells (Hwang et al, 2000;Mori et al, 2006;Geiger et al, 2010Geiger et al, , 2011Zou et al, 2010;Brandt et al, 2012;Scherzer et al, 2012;Latz et al, 2013;Gutermuth et al, 2013;Zhao et al, 2013;Zhou et al, 2014). The previous reports have revealed that plant ion channels and transporters are regulated by members of the CIPK (CBL-interacting protein kinase) family, another Ca 2+ -regulated protein kinase family, such as AKT1 regulation by CIPK23 (Xu et al, 2006;Wang and Wu, 2013) and Na + /H + antiporter (SOS1) regulation by CIPK24 (Xiong et al, 2002).…”
Section: Ca 2+ -Mediated Protein Phosphorylation: a Universal Regulatmentioning
confidence: 99%
“…CNGC-mediated Ca 2+ and K + current recordings in HEK293T cells were performed as described (41). For whole-cell Ca 2+ current recordings in Arabidopsis pollen tube protoplasts, protoplast isolation was carried out as described (46). cGMP was freshly added each day.…”
Section: Methodsmentioning
confidence: 99%
“…3 A and B), as previously reported (41). To test whether the point mutations R491Q and R578K impaired the activation of CNGC18 in vivo, we isolated pollen tube protoplasts (46) and measured the whole-cell inward Ca 2+ currents using a patch-clamping technique (32). In comparison with background currents in a cGMP-free condition, large currents were triggered by the intracellular application of 100 μM cGMP in WT (Fig.…”
Section: The Transmembrane Domains Of Cngc18 Are Essential For Pollenmentioning
confidence: 99%
“…Even more, single isoforms, for example, CPK21 in abscisic acid signaling or CPK5 in pathogen-associated molecular pattern (PAMP)-triggered innate immunity, were shown to play a dual role in rapid stress signal transduction and propagation on the one hand and in long-term, phytohormonemediated adaptive (and in last consequence developmental) processes on the other hand. However, much less is known about CPKs regulating plant development a priori, with the only exception of CPKs characterized in mediating single cell growth of pollen tubes (Myers et al, 2009;Gutermuth et al, 2013;Zhao et al, 2013;Zhou et al, 2014).…”
Section: Introductionmentioning
confidence: 99%